The safety handling of cytotoxic drugs - Abdul Rashid, Abdul Mukmin; Othman, Hapsah; Mohamad Zabidi, Suraiya Bani (2008)
Cytotoxic drugs are useful to kill or inhibit tumour growth or cell reproduction in treatment of chemotherapy. Cytotoxic drugs such as Epirubicin, Cyclophosphamide and many others have been found to be mutagenic, teratogenic and carcinogenic, So, the handling, preparation, administration and disposal of these drugs may constitute an occupational hazard.